The journey of humanity : the origins of wealth and inequality - Galor, Oded, 1953- (Dutton, 2022)
"Why are humans the only species to have escaped - only very recently - the subsistence trap, allowing us to enjoy a standard of living that vastly exceeds all others? And why have we progressed so unequally around the world, resulting in the great disparities between nations that exist today? Immense in scope and packed with astounding connections, Galor's gripping narrative explains how technology, population size, and adaptation led to a stunning "phase change" in the human story a mere two hundred years ago. But by tracing that same journey back in time and peeling away the layers of influence - colonialism, political institutions, societal structure, culture - he arrives also at an explanation of inequality's ultimate causes: those ancestral populations that enjoyed fruitful geographical characteristics and rich diversity were set on the path to prosperity, while those that lacked it were disadvantaged in ways still echoed today. As we face ecological crisis across the globe, The Journey of Humanity is a book of urgent truths and enduring relevance, with lessons that are both hopeful and profound: gender equality, investment in education, and balancing diversity with social cohesion are the keys not only to our species' thriving, but to its survival." --Publisher.